Pelaksanaan Eksekusi Barang Jaminan pada PT. Nusa Surya Ciptadana Cabang Soe dalam Perspektif Undang-Undang Nomor 42 Tahun 1999 Tentang Jaminan Fidusia - Dicky Kolodikson Selan; Agustinus Hedewata; Husni Kusuma Dinata (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
The purpose of this research is to analyze the implementation of the execution of collateral at Pt. Nusa Surya ciptadana soe branch in the perspective of Law Number 42 of 1999 concerning fiduciary guarantees. The research method used is empirical research so that the data sources used are primary data sources and secondary data. Primary data is obtained from interviews with sources and secondary data by visiting objects to obtain the necessary information. The conclusion of this research is that in the process of executing a collateral object at PT Nusa Surya Ciptadana Soe Branch, it is carried out in accordance with the provisions of Article 29 paragraph (1) letter c and the provisions of Article 15 paragraph (3) of Law Number 42 of 1999 concerning Fiduciary Guarantees. The legal consequences arising against the debtor, namely the existence of an agreement so that the creditor in withdrawing fiduciary collateral goods is not secured by the police and not through a letter of determination through the district court, causing an imbalance in the position between the creditor and the debtor. Based on this research, the researcher suggests that the financing institution in withdrawing and selling the fiduciary guarantee object needs to make a derivative regulation of the Constitutional Court's decision governing the implementation of the execution of fiduciary guarantees in order to maintain a balance so that the proceeds from the sale of the guarantee object do not harm both parties can change the provisions in the Fiduciary Guarantee Law regarding when the debtor is said to be in breach of promise and the need to outline the mechanism of the District Court guidelines. For the Community, before agreeing to a principal agreement, it is necessary to understand the contents of the clause of an agreement so that the desired breach of promise does not occur.